The quality of staff development among academic and administrative staff: Case study in Sultan Idris Education University - Ajis, Mohd Na'eim (2008)
Staff development is a vital and significant aspect in the organization.As far as staff development is concern, the role of human resources is very important to mobilise the organization to competetive level.The study aims to determine the level of quality in staff development among academics and administration staff in Sultan Idris Education University (UPSI).The level of quality in staff development has been divided with 3 dimensions (policy, programme and procedure).Besides, the study was conducted to determine the differences between the level of staff development based on selected variables such gender, department, service scheme and service length. Generally, the quality of staff development for academics and administrative staff in UPSI is moderate.In other words, the staff development in UPSI is acceptable by their staff.